Analysis of Iron and Lead Levels in Groundwater in Sub-Urban Areas of Palembang (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Access to clean water in Indonesia is one of the biggest problems. The main problem faced by the community is due to limited water resources and the problem of limited water quantity. Hence, they are unable to meet the increasing needs of the community. The decline in water quality is due to domestic and industrial waste entering water bodies. The influence of human activities so that pollutants entering the environment's surface, water, and groundwater increases yearly. Toxic and dangerous substances cause many problems to the environment and health. One of the harmful poisonous substances is heavy metals. This observational research is descriptive-analytic by testing the levels of metal iron (Fe), Lead (Pb), and pH of residents' well water. The research sample was collected using a sample grabber for the well water residents of Talang Betutu, Palembang. Samples were examined in the laboratory on the same day. The sample in this study amounted to 7 samples of residents' well water, which is still used for daily activities such as bathing and washing. Examination of heavy metals using a Uv Vis Spectrophotometer. The results showed that all residents' samples contained Fe and Pb at levels that did not exceed the quality standards. The chronic impact of consuming water containing heavy metals must be a concern because it lasts for a specific time.